Factors Related to the Economic Self-Reliance of People in Pakxeng District, Luang Prabang Province - SIOUDOMPHAN, Soutthavone; Saleumsack, Metkham; Layaseng, Somyot (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aims to 1) study the overall situation of economic self-reliance and 2) analyze the relationship between factors that affect the ability of people to be economically self-reliant in PakXeng district, Luang Prabang province. This study used a quantitative research method, targeting the people of PakXeng district in Luang Prabang province among 203 household. Data was collected using a questionnaire, and basic statistics were applied to determine percentages, sums, and frequency distributions, along with correlation analysis (Chi-Square) for data analysis. The study found that people have stable, durable, and safe housing; self-reliance in income expenditure and family savings can be achieved at 56.29%; and there is no debt from borrowing. At the same time, there are many family assets that can help families be self-reliant, such as land for livelihood and livestock. Most people do not keep a family income-expenditure account because they still lack financial knowledge and experience and have never done it before. Family economic promotion activities that can help families be self-reliant include home gardening, animal husbandry activities, activities to promote secondary employment, and activities to collect non-timber forest products. For factors related to the economic self-reliance of people in the PakXeng district, Luang Prabang province, it was found that factors related to family savings, home gardening activities, animal husbandry activities, cost of living, and natural disasters were statistically significant at the 0.01 level; factors related to the number of members who can generate income, housing security, highest level of education of family members, keeping a family income-expenditure account, and non-timber forest product collection activities were statistically significant at the 0.05 level; and the number of family members was related to the economic self-reliance of people with a statistical significance level of 0.1.